2010
DOI: 10.1111/j.1442-2050.2010.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary self-expanding metallic stents and pneumatic dilation for the treatment of achalasia: a prospective study with a long-term follow-up

Abstract: The present study compares the efficacy of a self-expanding metallic stent (SEMS, diameter of 30 mm) and pneumatic dilation for the long-term clinical treatment of achalasia. A total of 155 patients diagnosed with achalasia were allocated for pneumatic dilation (n= 80, group A) or a temporary, 30-mm diameter SEMS (n= 75, group B). The SEMSs were placed under fluoroscopic guidance and removed by gastroscopy 4-5 days after placement. Data on clinical symptoms, complications, and long-term clinical outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…A statistically significant reduction was observed in dysphagia, regurgitation, chest pain, and LES pressure in the expandable stent group compared to the pneumatic dilation group maintained through the end of the study at 10 years [28]. These findings are similar to two other recent studies [29,30], but differ from earlier pilot studies that suggested an unlikely future for stents in this disease [31]. Complications during these studies included stent migration (3%), although all stents were eventually removed endoscopically, chest pain (42%), and bleeding (16%).…”
Section: Self-expanding Stentssupporting
confidence: 93%
“…A statistically significant reduction was observed in dysphagia, regurgitation, chest pain, and LES pressure in the expandable stent group compared to the pneumatic dilation group maintained through the end of the study at 10 years [28]. These findings are similar to two other recent studies [29,30], but differ from earlier pilot studies that suggested an unlikely future for stents in this disease [31]. Complications during these studies included stent migration (3%), although all stents were eventually removed endoscopically, chest pain (42%), and bleeding (16%).…”
Section: Self-expanding Stentssupporting
confidence: 93%
“…Previous studies adopted a period of 3 to 7 days to remove the stents, and complications such as pain and bleeding occurred more frequently in the stent group than in the balloon dilation group . Short‐period SEMS placement was also associated with significantly higher clinical remission rates during the follow‐up periods . In our study we removed the stents one month after placement and no difficulties were encountered during the dislodging operation.…”
Section: Discussionmentioning
confidence: 77%
“…At least three Chinese series compared the efficacy and safety of esophageal SEMS versus PD in a large number of patients [72][73][74]. The overall results of all these series demonstrated a higher clinical remission rate with a 30 mm-SEMS compared to PD (83-89% vs 0-42%, respectively).…”
Section: Esophageal Stentingmentioning
confidence: 93%
“…Over the last 15 years, some studies evaluated the efficacy and safety of the procedure [68][69][70][71], and some comparative trials versus PD are also available [72][73][74]. A variety of stent models have been used in the published series: differences included mesh design, presence of a covering and diameter.…”
Section: Esophageal Stentingmentioning
confidence: 98%